PERAN NEGARA DALAM MENJAMIN KEBUTUHAN RAKYATNYA STUDI KASUS STRATEGI KEAMANAN ENERGI TIONGKOK DI KAZAKHSTAN (2000-2014) - Roby Rakhmadi; Agil Kurniadi; Ali Abdullah Wibisono (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2021)
This research explores China’s strategy in Kazakhstan in pursuing it’s energy security from 2000 till 2014. For China, energy security is vital for the continuation of it’s economic growth and people wellfare so that they take every risk bravely to ensure it’s fulfillment. From Kazakhstan, China is looking forward to move freely in Central Asia region by means of constructing pipeline infrastructure to carry oil and gas into it’s territory. Through this research writer formulate problem why China develop pipeline strategy in Kazakhstan for ensuring their energy supply. This research purpose is to understand China’s pipeline strategy in ensuring the link of energy supply. Using Mason Willrich Theory, China as importer country must ensure supply from abroad because China do not have much energy reserves in it’s territory. Data processing is conducted by qualitative methodology. The final result of this research such as first, development of oil and gas pipeline built by China is the chance to get direct energy source from the producer country. Second China try to increase relations in all of sectors which began from energy. Third, China try to form interdependence condition with Central Asian States as energy supplier and China as producer of finished goods. The writer get conclusion that final results is tested scientifically.